ADDITIVE MANUFACTURING THROUGH 3D PRINTING FDMFUSED DEPOSIT MODELING OF PRESS BUSH - Sorin Alexandru FICĂ; Andrei DIMITRESCU; Claudiu BABIȘ (Fiabilitate şi Durabilitate)
This paper highlights both theoretically and experimentally the use of 3D printing technology, using Fused Deposition Modeling technology. The part that has been printed is the press bushing for the flushing head of the FA100, FA125, FH150 and FG40 water drilling rigs. The proposed work falls within the framework of green technologies, friendly to the environment and within the projects for the realization of industrial parts by additive methods, respectively by 3D printing. This technology offers many advantages compared to the classic manufacturing technologies of that part both in terms of harmful emissions, high energy consumption and the final price of the part.